2007
DOI: 10.1103/physrevb.76.054449
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced magnetization reversal inNiFeCuCoAunotched mesoscopic bars

Abstract: In-plane current-induced and field-induced magnetization reversal in notched 2.1 m longϫ 270 nm wide pseudo-spin-valve NiFe/ Cu/ Co/ Au thin-film bars has been characterized and compared with the results of a three-dimensional micromagnetic model. The reversal of the soft NiFe layer is influenced by the magnetostatic fields of the hard Co layer, which can initiate switching of the NiFe layer from both ends of the bars, allowing for the existence of field-induced magnetic configurations containing one or two do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Clear changes in the XMCD contrast during the application of a current pulse revealed that the NiFe magnetization tilts by a relatively large angle in the direction transverse to the nanowires. Even if the Oersted field is not specific to SV nanowires, 52 its impact is increased in such devices because of its opposite action on the Co and the NiFe magnetizations. In particular, the dipolar interaction tends to amplify the opposite magnetization tilts initiated in NiFe and Co layers by the Oersted field.…”
Section: Discussionmentioning
confidence: 99%
“…Clear changes in the XMCD contrast during the application of a current pulse revealed that the NiFe magnetization tilts by a relatively large angle in the direction transverse to the nanowires. Even if the Oersted field is not specific to SV nanowires, 52 its impact is increased in such devices because of its opposite action on the Co and the NiFe magnetizations. In particular, the dipolar interaction tends to amplify the opposite magnetization tilts initiated in NiFe and Co layers by the Oersted field.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was shown that the contribution of the Oersted field and not only STT is needed to explain the magnetization reversal in trilayered pillars induced by a current flowing perpendicular to the plane of the layers [4,5]. For inplane currents, H Oe has been invoked to explain magnetization reversal in mesoscopic NiFe/Cu/Co/Au bars [6] and the resonant depinning of constricted domain walls (DWs) in NiFe/Cu/Co trilayers [7].…”
mentioning
confidence: 99%
“…For instance, it was shown that the contribution of the Oersted field and not only STT is needed to explain the magnetization reversal in trilayered pillars induced by a current flowing perpendicular to the plane of the layers. 4,5 For in-plane currents, H Oe has been invoked to explain magnetization reversal in mesoscopic NiFe/Cu/Co/Au bars 6 and the resonant depinning of constricted domain walls (DWs) in NiFe/Cu/Co trilayers. 7 Several studies on the effects of current pulses on the magnetization of nanostripes, mainly concerning currentinduced domain-wall motion (CIDM), have been based on the observation of the domain structure before and after the application of a current pulse.…”
mentioning
confidence: 99%
“…Above this threshold the profile of the magnetization is no longer rigid and there is a nucleation of more complex DWs such as vortex or antivortex walls. An important aspect in the study of the interaction of current and magnetization is the limited impact of the Oersted field produced by the current in long magnetic stripes [23,[41][42][43], compared to wider geometries such as magnetic disks [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%